2015
DOI: 10.4278/ajhp.130218-quan-72
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Controlled Trial of a Nutrition Intervention Program in a Multiethnic Adult Population in the Corporate Setting Reduces Depression and Anxiety and Improves Quality of Life: The GEICO Study

Abstract: A dietary intervention improves depression, anxiety, and productivity in a multicenter, corporate setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 57 publications
3
109
0
2
Order By: Relevance
“…The observed association of dairy intake and depression risk is less clear and is likely also to be affected by reverse causality. These results are partly in line with previous work, including work showing a vegan diet improved depression in the general population ( 59 ). A whole food plant-based diet has been recommended for people with MS and more widely for general health ( 60 ).…”
Section: Discussionsupporting
confidence: 92%
“…The observed association of dairy intake and depression risk is less clear and is likely also to be affected by reverse causality. These results are partly in line with previous work, including work showing a vegan diet improved depression in the general population ( 59 ). A whole food plant-based diet has been recommended for people with MS and more widely for general health ( 60 ).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, TSAI and co-workers (2012) reported that vegetables, but not fruit, were protective against depressive syndrome in older Taiwanese people. In clinical trials also, vegan diets have improved mental health (KATCHER et al, 2010) and decreased anxiety (AGARWAL et al, 2014). The reason that we did not fi nd an association between vegetable dietary pattern and psychological distress may be the method of cooking vegetables.…”
Section: Resultsmentioning
confidence: 72%
“…Therefore prospective randomized controlled studies on dietary effects are needed, with one starting at the moment in Australia [90]. In a quasi-experimental study, which examined the impact of a vegan diet on emotional well-being and productivity a weekly dietary instruction for 18 weeks resulted in an improvement in depression, anxiety, and productivity in 292 individuals [94]. Interestingly, vegetarians reported better mood than omnivores despite their negligible intake of EPA/DHA [96,97], which has also been confirmed in a parallel arm, interventional two-week randomized controlled trial [96,97] on a 2 week subclinical level in healthy volunteers who consumed vegetarian food [96,97].…”
Section: Association Studies Between Depression and Dietary Habitsmentioning
confidence: 99%